UU No.20 Th.2000 Perubahan UU No.21/1997 ttg bea perolehan hak atas tanah dan bangunan - [Tidak Terdaftar] (Myda, 2000)
UU No.20 Th.2000 Perubahan No.21/1997 ttg bea perolehan hak atas tanah dan bangunan